Effects of co-overproduction of Rubisco and chloroplast glyceraldehyde-3-phosphate dehydrogenase on photosynthesis in rice. Issue 3 (4th May 2021) - Suzuki, Yuji; Ishiyama, Keiki; Cho, Ayaka; Takegahara-Tamakawa, Yuki; Wada, Shinya; Miyake, Chikahiro; Makino, Amane
ABSTRACT: The capacity for regeneration of the substrate for Rubisco, ribulose 1, 5-bisphosphate (RuBP), is one of the candidates for the bottleneck in photosynthesis in transgenic rice plants with overproduction of Rubisco. As the overproduction of chloroplast glyceraldehyde-3-phosphate dehydrogenase (GAPDH) was suggested to slightly enhance RuBP regeneration capacity, transgenic rice plants with co-overproduction of Rubisco and GAPDH were generated to improve photosynthesis. The amount of Rubisco increased by 8% to 18%, whereas GAPDH activity increased to 2.1- to 3.2-fold that of the wild-type. However, the rate of CO2 assimilation did not increase under conditions of high irradiance and different [CO2 ] partial pressures. The possibility that photosynthesis in the co-overproduced plants was co-limited by Rubisco, GAPDH, and other unknown factors is discussed.